Osteonecrosis of the femoral and Humoral heads in sickle disease patients: Risk factor, Comorbiditis - Zenat Khired; Kholoud O. Alzain; Abdulaziz A. Hakami; Abdulrahman M. Yaqoub; Khalid Y. Muqri; Majd H. Moafa; Elaf H. Madkhli (Elsevier, 2024)
Objectives: AVN is the most common in Sickle Cell Disease patients, as SCD is common in the Jazan region of Saudi Arabia. The risk factors, and comorbidity regarding AVN of hip and shoulder joints in SCD patients were investigated in this study. Methods: This retrospective cohort study was conducted at the two biggest hospitals in the Jazan region. A valid data collection sheet was used to collect information of SCD patients admitted to the wards or during follow-up. Staging for HAVN and SAVN was based on FICAT classification guidelines. Descriptive statistics and multivariate logistic regression were utilized. Results: total number of participants is 257, and 99 (38.5%) were under 14 years of age. About half of the participants are (134) females. Regarding participants' hemoglobin type, 78.6% had SCD, while 21.4% had sickle thalassemia. The occurrence of HAVN and SAVN is 14.8% and 5.4%, respectively. Of the 38 HAVN participants, 26.3% had comorbidities, and 5.3% had hypertension. The SAVN participants didn't report diabetes or hypertension. The vascular occlusive crisis is the most significant complication associated with SCD. Multivariate logistic regression determined some risk factors for SAVN and HAVN. Conclusion: AVN is a frequent consequence of SCD, where the incidence rises with age. The vascular necrosis is the most significant complications. Continuing research on the prevention and non-surgical treatments of AVN caused by SCD must remain a top focus.